2-Hydroxy-5-methylbenzophenone oxime(HMBO) as an Analytical Reagent for Gravimetric Determination of Cu(II) - S. K. Shingadia; K. K. Desai (E-Journal of Chemistry)
2-Hydroxy-5-methylbenzophenone oxime (HMBO) was developed as a new analytical reagent for the gravimetric determination of divalent copper ion. In pH rang of 3.0 to 6.0, the reagent gives a buff colored precipitate with Cu(II). Job’s method and mole ratio method revealed that the stoichiometry of the complex is 1:2 (metal: ligand). Beer’s law is obeyed up to 61.25 ppm of Cu(II). Molar absorptivity and Sandell’s sensitivity at 400 nm were found to be 6.32 × 102 L mol -1 cm-1 and 0.359 μg/cm2 respectively. The stability constant of Cu(II)-HMBO complex is found to be 2.43 × 109. Gibb’s free energy change for complex formation reaction was found to be -12.88 Kcal/mol. The reagent can be used for the analysis of brass and alloy.